Standardizing hysteroscopy teaching: development of a curriculum using the Delphi method - Neveu, Marie-Emmanuelle; Debras, Elodie; Niro, Julien; Fernandez, Hervé; Panel, Pierre (Surgical endoscopy, 2017)
Background Hysteroscopy is performed often and in many indications but is challenging to learn. Hands-on training in live patients faces ethical, legal, and economic obstacles. Virtual reality simulation may hold promise as a hysteroscopy training tool. No validated curriculum specific in hysteroscopy exists. The aim of this study was to develop a hysteroscopy curriculum, using the Delphi method to identify skill requirements. Methods Based on a literature review using the key words “curriculum,” “simulation,” and “hysteroscopy,” we identified five technical and non-technical areas in which skills were required. Twenty hysteroscopy experts from different French hospital departments participated in Delphi rounds to select items in these five areas. The rounds were to be continued until 80–100% agreement was obtained for at least 60% of items. A curriculum was built based on the selected items and was evaluated in residents. Results From November 2014 to April 2015, 18 of 20 invited experts participated in three Delphi rounds. Of the 51 items selected during the first round, only 25 (49%) had 80–100% agreement during the second round, and a third round was therefore conducted. During this last round, 80–100% agreement was achieved for 31 (61%) items, which were used to create the curriculum. All 14 residents tested felt that a simulator training session was acceptable and helped them to improve their skills. Conclusions We describe a simulation-based hysteroscopy curriculum focusing on skill requirements identified by a Delphi procedure. Its development allows standardization of training programs offered to residents.